Pengaruh kebijakan dividen, struktur modal, dan Profitabilitas terhadap nilai perusahaan - Syahzuni, Barlia Annis; Muslimah, Bening Dini (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This study aims to examine the effect of dividend policy, capital structure, and profitability on firm value in the health sector listed on the Indonesia Stock Exchange (IDX) during the 2018-2021 period. In this study, the independent variables used, namely dividend policy proxied through Dividend Payout Ratio (DPR), capital structure proxied through Debt to Equity Ratio (DER), and profitability proxied through Return On Assets (ROA), and the dependent variable, namely firm value proxied through Tobin's Q modified. The population in this study were 17 companies and obtained research samples using purposive sampling technique as many as 9 companies for 4 years, resulting in 36 research samples. The data analysis method used is multiple linear regression analysis through the SPSS program. The results showed that the profitability variable had a partial positive effect on firm value, while the dividend policy variable and capital structure had no partial effect on firm value. Implications for investors and companies are expected to pay more attention to the funding used by the company in order to maintain business continuity with the funds owned.